HUBUNGAN ANTARA PEMAHAMAN GURU TENTANG POWER POINT PRESENTATION (PPT) DENGAN KUALITAS PPT YANG DIBUAT GURU (Studi Pada SMP Negeri 7 Tanjungpandan) - Meiti Silviana, - (2019)
Skripsi. Departemen Kurikulum dan Teknologi Pendidikan, Fakultas Ilmu Pendidikan, Universitas Pendidikan Indonesia, Tahun 2019. Pemanfaatan TIK khususnya power point presentation dalam proses pembelajaran harus didukung dengan pemahaman dan kemampuan dari Guru sebagai pengajar. Pemahaman Guru tentang power point presentation memiliki hubungan dengan kualitas ppt yang dibuat oleh Guru. Secara umum, rumusan masalah penelitian ini yaitu adakah hubungan yang signifikan antara pemahaman Guru tentang power point presentation dengan kualitas ppt yang dibuat Guru berdasarkan pendapat siswa di SMP Negeri 7 Tanjungpandan. Sedangkan secara khusus rumusan masalah penelitian ini adalah bagaimana pemahaman Guru tentang power point presentation dan bagaimana kualitas ppt yang dibuat Guru berdasarkan pendapat siswa di SMP Negeri 7 Tanjungpandan. Metode yang digunakan dalam penelitian ini adalah metode korelasional dengan rumus korelasi product moment dengan rumus simpangan dan deskriptif kuantitatif dengan menggunakan perhitungan ukuran dan persentase dari setiap kategori pemahaman Guru tentang power point presentation dan kategori kualitas ppt yang dibuat Guru. Instrumen yang digunakan yaitu angket yang terdiri dari angket untuk melihat pemahaman Guru dan angket untuk melihat kualitas ppt yang dibuat Guru. Teknik pengambilan sampel dilakukan dengan stratified random sampling. Simpulan umum dari penelitian ini ialah terdapat hubungan positif yang signifikan antara pemahaman Guru tentang power point presentation dengan kualitas ppt yang dibuat Guru di SMP Negeri 7 Tanjungpandan. Sedangkan simpulan secara khusus dari penelitian ini ialah Guru SMP Negeri 7 Tanjungpandan memiliki pemahaman yang tinggi mengenai power point presentation, dan kualitas tayangan power point presentation pun dinilai baik oleh siswa. Thesis. Curriculum and Educational Technology Department, Faculty of Science Education, Indonesia University of Education, 2019. Utilization of ICT especially for learning media based on power point presentations in the learning process must be supported by the understanding and ability of the teacher as an educator. Teachers are required to have competence in terms of technology. Teachers' understanding of power point based on learning media has a relationship with the quality of the slide presentation made by teachers in the view of State Junior High Schools students in Tanjungpandan District. In general, the problem formulation of this research is that there is a significant relationship between the teacher's understanding of learning media based on power point presentations and the quality of the slide presentation made by teachers in junior high school students' view in Tanjungpandan district. While specifically is how the teacher's understanding of learning media based on power point presentation and how is the quality of the slide presentations made by teachers in the view of State Junior High Schools students in Tanjungpandan District. The method used in this research is the correlational method with the product moment correlation with the deviation and quantitative descriptive formulas using the size and percentage calculation of each category of teacher's understanding of learning media based on power point presentation and the categories of slide presentation quality made by the teacher. The instrument used were two questionnaires consisting of a questionnaire to see the understanding of the teacher and a questionnaire to see the quality of the slide presentations made by the teacher. The sampling technique was done by cluster random sampling. The general conclusion of this study is that there is a very close and significant relationship between teachers' understanding of learning media based on power point presentations and the quality of slide presentations made by teachers in students' view. While the specific conclusion from this study is the teachers of State Junior High Schools in Tanjungpandan District have a high understanding of learning media based on power point presentations, and the quality of power point presentation slide is also rated good by students. Keywords: Teacher's Understanding, Learning Media, Power Point Presentation, Display Quality